The Effect of Delone and Mclean’s Information System Success Model on The Job Performance of Accounting Managers in Iraqi Banks - Sabah, Mohammed Ihsan Ahmed; Rashid, Umi Kartini; Nasuredin, Juzaimi; Hamawandy, Nawzad Majeed; Bewani, Hemn Adl Wali AL; Jamil, Diyar bdulmajeed (The journal of contemporary issues in business and government, 2021)
Organizations have taken into consideration the rapid shifts in the business environment, which made them consider implementing various strategies to face fierce worldwide market competition. Such a job performance has become increasingly challenging for many organizations, in general, and particularly in banks. This study aims at proposing system quality, information quality, and service quality utilizing user satisfaction to enhance job performance by evaluating the mediating function of user satisfaction in the association between system quality, information quality, and service quality and job performance in the Iraqi banking sector. A quantitative approach is used to obtain data from a survey (questionnaire) consisting of 55 items with a five-point Likert scale A total of 65 account managers participated in the Iraqi banking sector in the study. (a 91.5% response rate). The data analysis was conducted using Smart PLS 3.2.9. The findings of the path analysis of partial least squares (PLS) support variables in their hypothesized direct relationships with job performance. User satisfaction partially mediates the relationship between System Quality, Information Quality, Service Quality, and job performance. The paper advances several recommendations that can be beneficial for researchers to conduct further studies in this area as well as account managers in their efforts to enhance the job performance of organizations in the future.